INVESTIGATION OF VERTICAL FORCED VIBRATION IN THE LONGITUDINAL - VERTICAL PLANE OF A BINDER THAT SOFTENS THE CRUSH BETWEEN COTTON ROWS - Egamov, Nodirbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The forces acting on the bobbin due to moisture, density, and hardness of the tangle formed between rows of cotton were studied. Roll on in the longitudinal - vertical plane, in addition to the forward motion, the aggregate of the blade performs a forced oscillating motion in the vertical direction. Forced vibration motion of the roller in the vertical direction was studied. It was found that the force was linearly dependent on the amount and speed of the deformation of the coil under the influence of rolling. The sum of the forces arising from the variation of the physico-mechanical properties of the concrete was found.[1] It can be seen from the analysis that, for the given working conditions, the quality of the smoothing of the roller by the roller was achieved due to its total mass, that is, the parallelogram mechanism and the joint mass, the uniformity of the pressure spring, and the correct choice of the angle of deviation from the horizon during the operation of the parallelogram mechanism's longitudinal pullers.[2]